2022
DOI: 10.3389/fphys.2021.749255
|View full text |Cite
|
Sign up to set email alerts
|

Acute Gravitational Stress Selectively Impairs Dynamic Cerebrovascular Reactivity in the Anterior Circulation Independent of Changes to the Central Respiratory Chemoreflex

Abstract: Cerebrovascular reactivity (CVR) to changes in the partial pressure of arterial carbon dioxide (PaCO2) is an important mechanism that maintains CO2 or pH homeostasis in the brain. To what extent this is influenced by gravitational stress and corresponding implications for the regulation of cerebral blood flow (CBF) remain unclear. The present study examined the onset responses of pulmonary ventilation (V̇E) and anterior middle (MCA) and posterior (PCA) cerebral artery mean blood velocity (Vmean) responses to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…As in previous studies [ 31 , 39 ], the magnitude response and time response of CVR ( τ ) determined by CO 2 inhalation, the traditional index of CVR, were attenuated during 50° HUT ( p < 0.001, Figure 1 and p = 0.001, Figure 2 , respectively). The physiological mechanism explaining the orthostatic stress-induced attenuation in CVR remains unknown, but it has been speculated that the attenuated CVR may reflect a progressively reduced cerebrovascular reserve to compensate for the increasingly unstable systemic circulation during orthostatic stress, which could ultimately lead to cerebral hypoperfusion and syncope [ 31 , 39 ]. In addition, orthostatic stress could influence the cerebrovasculature, including ventilation-perfusion matching that is distributed across the zones of the lung during these posture changes and affects PaCO 2 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As in previous studies [ 31 , 39 ], the magnitude response and time response of CVR ( τ ) determined by CO 2 inhalation, the traditional index of CVR, were attenuated during 50° HUT ( p < 0.001, Figure 1 and p = 0.001, Figure 2 , respectively). The physiological mechanism explaining the orthostatic stress-induced attenuation in CVR remains unknown, but it has been speculated that the attenuated CVR may reflect a progressively reduced cerebrovascular reserve to compensate for the increasingly unstable systemic circulation during orthostatic stress, which could ultimately lead to cerebral hypoperfusion and syncope [ 31 , 39 ]. In addition, orthostatic stress could influence the cerebrovasculature, including ventilation-perfusion matching that is distributed across the zones of the lung during these posture changes and affects PaCO 2 .…”
Section: Discussionsupporting
confidence: 81%
“…Given this background, the aim of the present study was to examine the validity of the method (TFA) under spontaneous respiration without CO 2 inhalation for assessing CVR. In our recent study [ 31 ], we observed that orthostatic stress (50° head-up tilt, HUT) attenuated CVR determined by traditional methods (i.e., magnitude response or time response, τ ). In the present study, the change in CVR during 50° HUT from supine was assessed using the TFA between middle cerebral artery blood velocity (MCA V) and predicted PaCO 2 during spontaneous respiration (at the operating point) to compare with CVR indices determined using the traditional methods with a CO 2 inhalation challenge.…”
Section: Introductionmentioning
confidence: 99%